Selenoprotein DIO2 Is a Regulator of Mitochondrial Function, Morphology and UPRmt in Human Cardiomyocytes - Nils Bomer (MDPI AG, 2021)
Members of the fetal-gene-program may act as regulatory components to impede deleterious events occurring with cardiac remodeling, and constitute potential novel therapeutic heart failure (HF) targets. Mitochondrial energy derangements occur both during early fetal development and in patients with HF. Here we aim to elucidate the role of DIO2, a member of the fetal-gene-program, in pluripotent stem cell (PSC)-derived human cardiomyocytes and on mitochondrial dynamics and energetics, specifically. RNA sequencing and pathway enrichment analysis was performed on mouse cardiac tissue at different time points during development, adult age, and ischemia-induced HF. To determine the function of DIO2 in cardiomyocytes, a stable human hPSC-line with a DIO2 knockdown was made using a short harpin sequence. Firstly, we showed the selenoprotein, type II deiodinase (DIO2): the enzyme responsible for the tissue-specific conversion of inactive (T4) into active thyroid hormone (T3), to be a member of the fetal-gene-program. Secondly, silencing DIO2 resulted in an increased reactive oxygen species, impaired activation of the mitochondrial unfolded protein response, severely impaired mitochondrial respiration and reduced cellular viability. Microscopical 3D reconstruction of the mitochondrial network displayed substantial mitochondrial fragmentation. Summarizing, we identified DIO2 to be a member of the fetal-gene-program and as a key regulator of mitochondrial performance in human cardiomyocytes. Our results suggest a key position of human DIO2 as a regulator of mitochondrial function in human cardiomyocytes.